(untitled) (Eureka Journal of Humanities and Social Research, 2026)
This article analyzes the essence of the right to personal inviolability, its place in international and national law from a comparative legal perspective. The study compares the guarantees of personal inviolability in the new edition of the Constitution of the Republic of Uzbekistan and criminal procedural legislation with the experience of developed foreign countries (USA, Germany, Great Britain).